THE NEXUS BETWEEN FINANCIAL DEVELOPMENT AND ECONOMIC GROWTH; GHANAIN EXPERIENCE (Journal of the Management Sciences, 2024)
This study examined the nexus between financial development and economic growth in Ghana; Economic Growth is proxied with Gross Domestic Product Per Capita was used as the dependent variable while Gross Fixed Capital Formation, Foreign Debt, Foreign Direct Investment and Trade Openness were employed as independent variables. Secondary data analyzed, using descriptive statistics, unit root test, Johansen Co-integration, and ordinary least square methods of multiple regression. It was evident that Gross Fixed Capital Formation (GFCF) and Foreign Direct Investment (FDI) depicts positive and significant influences on Gross Domestic Product Per Capita while Foreign Debt (FD) and Trade Openness (OP) have negative and significant influence on Gross Domestic Product Per Capita. Hence, it is observed that there is a significant relationship between finance and economic development in Ghana. It is recommended that the Ghanaian financial development should be encouraged to support economic growth and development.
Keywords: Finance, Economic Development, Growth, Nigeria